(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article examines in detail the traditional customs and rituals of the Kyrgyz people associated with funerals, as well as their distinctive features and ideas about the world. The Kyrgyz, being one of the most ancient peoples of Central Asia, managed to preserve extensive knowledge, which was reflected in the formation of their ancient customs and traditions. This knowledge played a significant role in the development of human society and includes such religious and philosophical movements as animism, Tengrism, Vedism, shamanism, Zoroastrianism, Buddhism, Manichaeism and Islam. Thus, the Kyrgyz are one of the nations that attract significant interest due to their rich cultural and religious heritage. In the context of modern globalization and politics based on the principles of freedom of religion and democracy, there is a wide spread of various religious sects, including Islamic ones. This is having an unprecedented impact on the unique ancient traditions of the Kyrgyz, putting them at risk of extinction. In this regard, it is especially important to carefully study the funeral customs of the Kyrgyz, which are one of the key sources of information about the ancient religious ideas and worldviews of this people. The study of funeral rituals provides a valuable opportunity for a deep understanding of not only Kyrgyz culture, but also the culture of related Turkic peoples. This study can open new perspectives and shed light on many aspects of their spiritual and social development, making it extremely important and relevant.